Early excision and grafting versus conservative management in burns: A comparative study. - Rai, Pranil (2002)
ABSTRACT: This prospective study was done to compare early excision and grafting with conservative management in patients with burn. A total of 6 percent patients were included in the study which was conducted at the Burn and plastic unit, Bir Hospital over the period of 18 months from Magh,2057 to Asar,2059. One group comprising of 30 patients were subjected to early excision and grafting i.e. within 7 days of burn injury. The patients in the other group were treated conservatively i.e. repeated debridement during dressing and under general anaesthesia and split thickness skin grafting once the wound had healthy granulation. Among the 60 patients, 24 patients were in the age group 25-34 years and 15 patients were in the 15-24 years age group. The mean age was 32.47 years. The male to female ratio was 1:2. 96.7% of patients in this study had sustained flame burn and the chief mode of burn injury was accidental 86.7%. 53.3% of the patients had sustained 30-39% TBSA burn and 20.0% has sustained 20-29% TBSA burn. Majority of the patients in the EEG group were operated on the 5th post burn day and 4 patients had to be regrafted and stayed in the hospital for a longer period of time. The patients in the conservatively managed group had to undergo 2-4 sessions of debridement under general anaesthesia and 2-3 sessions of skin grafting. The hospital stay and the mortality rate between the two groups were compared. The hospital stay in the early excision and grafting group was shorter (mean 26 days) in comparison to the group treated conservatively (mean 35.7days) and the difference was statistically significant (p-value of 0.014). The mortality was lower in the group that had been subjected to early excision and grafting. It was 6.7% in the EEG group ad compared to 30.0% in the conservative group and the difference was statistically significant (p-value of 0.02). The study has shown that treatment of burn patients with early excision and grafting has superior results over conservative management I terms of hospital stay survival.